2021
DOI: 10.1016/j.jbo.2021.100397
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and reason for reoperation following non-invasive expandable endoprostheses: A systematic review

Abstract: Highlights Implant failure is the most common reason for revision of growing prostheses. Maximum prosthesis growth with a residual LLD is the most common mode of failure. Functional outcomes are good, but 1/ 5 patients have a persistent LLD over 2 cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Previous reports suggested that infection and local recurrence are the main reasons for failure 25,26 . The more specific types of implant failure consisted of insufficient maximal prosthesis lengthening; premature extension failure; prosthesis fracture; bushing or articulation wear 24 . In our study, only one patient had an infection.…”
Section: Effect Of Expandable Prosthesismentioning
confidence: 44%
See 3 more Smart Citations
“…Previous reports suggested that infection and local recurrence are the main reasons for failure 25,26 . The more specific types of implant failure consisted of insufficient maximal prosthesis lengthening; premature extension failure; prosthesis fracture; bushing or articulation wear 24 . In our study, only one patient had an infection.…”
Section: Effect Of Expandable Prosthesismentioning
confidence: 44%
“… 25 , 26 The more specific types of implant failure consisted of insufficient maximal prosthesis lengthening; premature extension failure; prosthesis fracture; bushing or articulation wear. 24 In our study, only one patient had an infection. Lower prosthesis complication rates reduced the risk of second intervention before replacement with a permanent prosthesis.…”
Section: Effect Of Expandable Prosthesismentioning
confidence: 55%
See 2 more Smart Citations
“…The first-generation lengthening prosthesis was designed by Dr. Scales and Stanmore in 1976. This prosthesis requires open surgery, which entails significant trauma, causing considerable discomfort, especially for patients who require multiple lengthening procedures ( Lex et al, 2021 ). A related study indicates that the infection of the prosthesis and postoperative complications, such as loosening of the prosthesis, is relatively high ( Schindler et al, 1997 ).…”
Section: Discussionmentioning
confidence: 99%